Protective role of salt in catalysis and maintaining structure of halophilic proteins against denaturation - Sinha, Rajeshwari; Khare, Sunil K. (Frontiers in Microbiology, 2014)
Search for new industrial enzymes having novel properties continues to be a desirable pursuit in enzyme research. The halophilic organisms inhabiting under saline/ hypersaline conditions are considered as promising source of useful enzymes. Their enzymes are structurally adapted to perform efficient catalysis under saline environment wherein n0n-halophilic enzymes often lose their structure and activity. Haloenzymes have been documented to be polyextremophilic and withstand high temperature, pH, organic solvents, and chaotropic agents. However, this stability is modulated by salt. Although vast amount of information have been generated on salt mediated protection and structure function relationship in halophilic proteins, their clear understanding and correct perspective still remain incoherent. Furthermore, understanding their protein architecture may give better clue for engineering stable enzymes which can withstand harsh industrial conditions. The article encompasses the current level of understanding about haloadaptations and analyzes structural basis of their enzyme stability against classical denaturants.